THE EFFECTIVENESS OF SERVICE LEARNING MODEL ASSISTED BY FLASH CARD MEDIA ON STUDENTS' ENVIRONMENTAL AWARENESS - Defi Yusfika Dani; Hanin Niswatul Fauziah (Universe, 2022)
This study aims to determine the effectiveness of service learning model assisted by flash card media to increase student’s environmental awareness at SMPN 1 Sambit Ponorogo. The samples in this study were class VII A (experimental) and class VII C (control) with a total of 40 students. Data were collected by distributing test questions before and after the implementation of learning model. The learning model applied to the control class was lecturing model, while the experimental class was service learning model assisted by flash card media. The data that has been obtained were analyzed by t-test using Minitab software. The results showed that the service learning model assisted by flash card media was effective to increase students' environmental awareness. This is due to service learning model is able to direct students to apply their knowledge in solving environmental problems around them. Besides that, the use of flash card media can increase students' enthusiasm for learning due to it was packaged in educational games.